Metabolic syndrome and depressive symptoms among rural Northeast general population in China - Shasha Yu; Hongmei Yang; Xiaofan Guo; Liqiang Zheng; Yingxian Sun (BMC, 2017)
Abstract Background Previous researches aiming to estimate the association between metabolic syndrome and depressive symptoms come out with inconsistent results. Besides, most of them are conducted in the developed areas. There is lack of the data from rural China. The aim of this study is to confirm whether gender difference exists among the relationship between MetS, metabolic components and depressive symptoms in the rural Chinese population. Methods A cross-sectional analysis enrolled 11430 subjects' aged ≥35 from rural Northeast China. Metabolic and anthropometric indicators were measured according to standard methods. Depressive symptoms were defined using the Patient Health Questionnaire-9 (PHQ-9). Results The prevalence of depressive symptoms was 6% among rural Northeast general population and the prevalence of MetS and its components were 39.0% for MetS, 42.9% for abdominal obesity, 67.1% for elevated blood pressure, 47.1% for hyperglycemia, 32.1% for hypertriglyceridemia, 29.5% for low HDL-C. Depressive symptoms were associated with triglyceride component (OR = 1.24, 95%CI: 1.05-1.46, P = 0.01) but not MetS (OR = 1.11, 95%CI: 0.94-1.30, P = 0.23). Moreover, depressive symptoms were associated with triglyceride component (OR = 1.21, 95% CI = 1.00-1.47, P = 0.05) in women only. But once adjusted for menopause status, depressive symptoms were no longer statically associated with triglyceride component (OR = 1.20, 95% CI = 0.99-1.46, P = 0.07). Conclusions Depressive symptoms were associated with triglyceride component but not MetS in rural Chinese population. Routine lipid screening should be recommended among rural depressed residents especially among female.